If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -4x = 6 + -8x Solving -18 + -4x = 6 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -18 + -4x + 8x = 6 + -8x + 8x Combine like terms: -4x + 8x = 4x -18 + 4x = 6 + -8x + 8x Combine like terms: -8x + 8x = 0 -18 + 4x = 6 + 0 -18 + 4x = 6 Add '18' to each side of the equation. -18 + 18 + 4x = 6 + 18 Combine like terms: -18 + 18 = 0 0 + 4x = 6 + 18 4x = 6 + 18 Combine like terms: 6 + 18 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| 174-4x=23x+18 | | 8a+5a+5b-3b= | | 2x+20=9x-27 | | -16=0.2n | | 3/5=6 | | 122-3x=15x+24 | | 5(3x+1)=4x-8x | | 1+4m+5m^2+2m^3=0 | | 1-3+7=6 | | 5u-10v= | | 12-9x=35-16x | | x^3-9x^2+24x+1=0 | | 4+3*5=x | | 4x-x-2=34 | | 3bc=12+9bc | | s+808=57 | | -(7-4x)=7 | | 114=2u | | f29=7 | | 11x+11=4x+158 | | 42+5x=9-8x | | v+66=993 | | 6*8=0 | | 284-7x=38x+24 | | 7x+2x-3=5x+9 | | q+407=73 | | -19x-21=35-x | | xy=29 | | 20x^2+60x+45=0 | | q+ -407= -73 | | 3x+1=6x-2 | | r+450=996 |